Henryk Dembiński (1908-1941) i jego poglądy na istotę samorządu - Dobkowski, Jarosław (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2020)
The article presents Henryk Dembiński's views on the essence of local government through the prism of the notion of public-law personality. His key finding is that the ideological and sociological context is important, but not conclusive as to the legal essence of local government. In this respect, one can disagree on Henryk Dembiński's downgrading or even denying the public-law personality of the local government. His views are a particular point of view that must be taken into account all the time.